(untitled) (Asian Journal of Agriculture, 2022)
Abstract. Choirunnisa LF, Solichatun, Yunus A. 2022. Effect of vermicompost and biostarter on the growth and photosynthetic rate of Echinacea purpurea. Asian J Agric 6: 35-39. Echinacea purpurea (L.) Moench, or purple coneflower, is a medicinal plant that originated in North America and began to cultivate in Indonesia. A proper method is needed to improve its growth and development to adjust and cultivate in tropical areas like Indonesia. This study aimed to determine the effect of vermicompost and biostarter on the growth and photosynthetic rate of E. purpurea. Therefore, Split-Plot Randomized Complete Block Design was used. Two factors of this study were organic materials such as vermicompost and biostarter. Both can increase plant growth and the photosynthetic rate of E. purpurea. The dosages of vermicompost were 0, 40, 60, and 80 g/plant, and different types of biostarter from Banana peel waste and EM. This study also investigated data that included plant height and width, leaf numbers, leaf area, photosynthetic and transpiration rate, and stomata conductance. The study showed that the treatment of 80 g/plant vermicomposts and EM highest resulted in plant height (73,6 cm), leaf numbers (82), and stomatal conductance (0,4585 mol m-2s-1). Moreover, the leaf area (87,21 cm2) and photosynthetic rate (0,6839 µmol m-2s-1) showed the highest result with the treatment of 80 g/plant vermicomposts and biostarter from Banana peel waste. On the other hand, the treatment of 60 g/plant vermicompost showed the best result on plant width (50,25 cm) also transpiration rate (0,2390 mmol m-2s-1). This study concluded a significant effect between vermicompost and biostarter on the growth and photosynthetic rate of E. purpurea.